Origen y caracteres estructurales del poder punitivo en el Perú antiguo desde la Criminología Cautelar - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
The genealogy of punitive power in Peru, is a matter little treated, therefore this article summarizes the thesis: "Archeology from Precautionary Criminology on the origin and structural characteristics of punitive power in ancient Peru", the same one that deals with the problem of the lack of knowledge about the origins of the punitive power of ancient Peru, for this reason the investigation answered the question: When was the origin and how are the structural characters of the punitive power in the Peruvian penal system of the Pre-Inca and Inca States, from Precautionary Criminology? and the objective of explaining when was the origin and how are the structural characters of the punitive power in the penal system of the Pre-Inca and Inca States from the Precautionary Criminology. The research was of qualitative design and used the archaeological and historical method; As a result, it was possible to trace the punitive power in ancient Peru and conclude that the verticalization of the theocratic states of ancient Peru (Pre-Inca and Incas) originated the punitive power and was structurally manifested in selectivity, differential social training, impunity of the white collar, inverse relationship between economic power and punitive vulnerability, and surveillance.